2009
DOI: 10.1084/jem.20090896
|View full text |Cite
|
Sign up to set email alerts
|

Decreased TNF-α synthesis by macrophages restricts cutaneous immunosurveillance by memory CD4+ T cells during aging

Abstract: Immunity declines during aging, however the mechanisms involved in this decline are not known. In this study, we show that cutaneous delayed type hypersensitivity (DTH) responses to recall antigens are significantly decreased in older individuals. However, this is not related to CC chemokine receptor 4, cutaneous lymphocyte-associated antigen, or CD11a expression by CD4+ T cells or their physical capacity for migration. Instead, there is defective activation of dermal blood vessels in older subject that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
165
1
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(186 citation statements)
references
References 57 publications
13
165
1
7
Order By: Relevance
“…Several reports have demonstrated that the fraction and number of peripheral and tissue-located Tregs increase with age (Gregg et al 2005;Vukmanovic-Stejic et al 2006;Lages et al 2008;Agius et al 2009;Booth et al 2010). Similar to the entire CD4 + T cell population, the fraction of regulatory recent thymic emigrants and Tregs with a naïve phenotype decreases with increasing Tregs with a memory phenotype (Gregg et al 2005;Booth et al 2010).…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have demonstrated that the fraction and number of peripheral and tissue-located Tregs increase with age (Gregg et al 2005;Vukmanovic-Stejic et al 2006;Lages et al 2008;Agius et al 2009;Booth et al 2010). Similar to the entire CD4 + T cell population, the fraction of regulatory recent thymic emigrants and Tregs with a naïve phenotype decreases with increasing Tregs with a memory phenotype (Gregg et al 2005;Booth et al 2010).…”
Section: Cd8mentioning
confidence: 99%
“…This T cell subset is less well studied than T and B cells, but similarities to what is known for αβTCR + T cells remain clear: the repertoire of γδTCR + T cells and the cell counts decrease with age (Giachino et al 1994;Colonna-Romano et al 2002;Argentati et al 2002;Re et al 2005;Andreu-Ballester et al 2012). The Treg population increases with age (Gregg et al 2005;Vukmanovic-Stejic et al 2006;Lages et al 2008;Agius et al 2009;Booth et al 2010), although the internal composition changes from a naïve to a memory phenotype (Gregg et al 2005;Booth et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…18,20,21,44,45 In addition, decreased macrophage TNF is critical in aging-associated immunity deficiency. 46 These studies highlight the essential role of TNF in human immunophysiology. Furthermore, using TNF to kill tumor cells has been proposed in cancer treatment 47 ; and exciting positive results have been reported in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy, noninflamed individuals, SMT may boost immune surveillance via enhanced macrophage TNF production (Figs 2 and 3). 9,35,46 This uses the beneficial feature of physiological TNF and may be one of the reasons why SMT is effective during wellness management for rather healthy individuals. 4 In inflammatory pain conditions, the early TNF spike produced by SMT may serve as a fresh stimulus, sensitizing and activating Tregs to the chronically high level of TNF.…”
Section: Discussionmentioning
confidence: 99%
“…This may, on one hand, be due to the fact that the formation of a skin test induration not only depends on the functionality of antigen-specific cells but also on their ability to be actively recruited to the injection site, which is defined by the local tissue environment (17). Both processes are known to be negatively affected by immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%